Impact of Brassica juncea biofumigation on viability of propagules of pernicious weed species. (5th March 2019) - De Cauwer, B; Vanbesien, J; De Ryck, S; Reheul, D
Summary: Biofumigation may be a promising tool for depletion of persistent weed seedbanks/bud banks. This technique is based on the incorporation of chopped glucosinolate‐rich plant biomass into the soil, upon which isothiocyanates with herbicidal properties are released. To gain acceptance by farmers and foster its implementation, the biofumigation process should be further optimised. This study elucidated the impact of biological (species), technical (burial depth, ground cover) and pedohydrological (temperature and moisture content) factors on efficacy of Brassica juncea biofumigation under (semi‐)natural conditions. In a first experiment (field experiment), seeds and vegetative propagules of various weed species were buried at different depths and exposed to different doses of fresh fine‐chopped B. juncea biomass in the presence or absence of a plastic ground cover. In a second experiment (container experiment), buried seeds of ten species were subjected to biofumigation at diverging soil organic matter content, soil moisture content and soil temperature. In a third experiment (dose–response Petri dish bioassay), unburied seeds of eight species were subjected to various doses of rehydrated B. juncea powder. Biofumigation efficacy was determined by analysing viability of treated and untreated propagules. In general, efficacy of biofumigation increased with decreasing burial depth and increasing B. juncea dose. Biofumigation was highly effective (mortality >85%) against small‐seeded species but less effective (mortality 0%–20%) against hard‐seeded and large‐seeded species at 200 t ha −1 . Vegetative propagules of Sonchus arvensis, Equisetum arvense and Convolvulus sepium were highly sensitive (mortality >90%) to biofumigation. Efficacy was most pronounced under moist warm incubation conditions, in the presence of a plastic ground cover.